2019
DOI: 10.5194/amt-12-4309-2019
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical depth comparison between GAW-PFR and AERONET-Cimel radiometers from long-term (2005–2015) 1 min synchronous measurements

Abstract: Abstract. A comprehensive comparison of more than 70 000 synchronous 1 min aerosol optical depth (AOD) data from three Global Atmosphere Watch precision-filter radiometers (GAW-PFR), traceable to the World AOD reference, and 15 Aerosol Robotic Network Cimel radiometers (AERONET-Cimel), calibrated individually with the Langley plot technique, was performed for four common or “near” wavelengths, 380, 440, 500 and 870 nm, in the period 2005–2015. The goal of this study is to assess whether, despite the marked tec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 89 publications
4
54
0
2
Order By: Relevance
“…The major surface aerosol networks include AERONET, which operates hundreds of stations around the globe [11]; SKYNET, which operates more than 60 stations globally with main focus on Asia [12]; and the Global Atmospheric Watch/Precision Filter Radiometer (GAW/PFR), which operates approximately 20 stations with long-term measurements [13,14]. Various homogenization activities for these different networks have been reported [15,16]. Data from these networks have been used frequently for climatological studies.…”
Section: Introductionmentioning
confidence: 99%
“…The major surface aerosol networks include AERONET, which operates hundreds of stations around the globe [11]; SKYNET, which operates more than 60 stations globally with main focus on Asia [12]; and the Global Atmospheric Watch/Precision Filter Radiometer (GAW/PFR), which operates approximately 20 stations with long-term measurements [13,14]. Various homogenization activities for these different networks have been reported [15,16]. Data from these networks have been used frequently for climatological studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we have used AOD data provided by the permanent AERONET-Cimel CE318-T reference instrument to compare the AOD derived from the EKO MS-711 spectroradiometer. The different Cimel references have been shown to have good AOD traceability with the GAW-PFR worldwide reference (Cuevas et al, 2019). The World AOD reference is maintained by the World Optical Depth Research and Calibration Center (WORCC) (Kazadzis et al, 2018b).…”
Section: Ancillary Information: Aeronet-cimel Sun Photometermentioning
confidence: 99%
“…Schmid et al, 1999;Kazadzis et al, 2014Kazadzis et al, , 2018aBarreto et al, 2014;Cuevas et al, 2019), mainly due to the establishment of aerosol measurement networks, such as AErosol RObotic NETwork (AERONET; Holben et al, 1998), the Global Atmosphere Watch (GAW), the Precision Filter Radiometer network (PFR, collectively GAW-PFR; Wehrli, 2000Wehrli, , 2005, the SKYNET sky radiometer network (Takamura and Nakajima, 2004), and Surface Radiation Budget Network (SURFRAD; Augustine et al, 2008). Recently, Cuevas et al (2019) conducted a study comparing AOD from AERONET-Cimel (1.2 • field of view (FOV)) with that of GAW-PFR (2.5 • FOV) by showing a difference of ∼ 3 % at 380 nm and ∼ 2 % at 500 nm; thus, GAW-PFR showed lower values when compared to AERONET-Cimel for AOD > 0.1. They demonstrated that this difference was due to the higher amount of dust near-forward scattering measured by GAW-PFR because of its larger FOV.…”
Section: Introductionmentioning
confidence: 99%
“…This station is managed by the Izaña Atmospheric Research Center (IARC), which is part of the State Meteorological Agency of Spain (AEMET). The elevation and the subtropical location of IZO, in the descending branch of Northern Hadley's cell, entail dry atmospheric conditions and the presence of pristine skies representative of the free troposphere most of the time (see [54][55][56], and the references therein). These privileged conditions have allowed a comprehensive measurement programme for atmospheric composition monitoring to be established at IZO for many years.…”
Section: Test Sitementioning
confidence: 99%
“…The IZO monitoring activities routinely participate in multiple international networks and databases, highlighting its role as an absolute calibration site for two of the most important ground-based photometer aerosol networks: NASA-AERONET and GAW precision-filter radiometers (GAW-PFR). In this sense, IZO is commonly used for optimal application of the Langley-Plot technique to a large number of activities, such as absolute direct sun/moon photometric calibration [30,56,58,59] or the retrieval of reference top-of-atmosphere (TOA) solar spectrum from the ground at different spectral ranges [60,61]. Refer to [55] for more details about IZO and its atmospheric monitoring programmes.…”
Section: Test Sitementioning
confidence: 99%